Colour patterns on Silurian orthocerid and pseudorthocerid conchs from Gotland – palaeoecological implications - Štěpán Manda; Vojtěch Turek (Estonian Journal of Earth Sciences, 2015)
The longitudinal colour pattern – an adaptively controlled feature functioning in cephalopods as camouflage – is described in two straight-shelled cephalopods from the Silurian of Gotland. A shell of the orthocerid Dawsonoceras annulatum (Sowerby) exhibits relatively broad longitudinal colour bands around the entire shell circumference, which in combination with transverse annuli and undulated growth ridges form a visually reticulate ornament. Such a combination is not known in other Silurian straight-shelled cephalopods. Dawsonoceras annulatum is the only known Palaeozoic cephalopod retaining an almost identical colour pattern in populations inhabiting different palaeo-continents. The shell of the pseudorthocerid Lyecoceras? columnare (Marklin) has densely packed narrow longitudinal colour bands on the entire smooth shell. In this feature the species is very similar to other Silurian and Ordovician pseudorthocerids. However, in Ordovician pseudorthocerids colour bands are restricted dorsally. The type of colouration described herein differs from that of Devonian and younger pseudorthocerids where the shell bears zig-zag bands. Longitudinal colouration around the entire shell circumference supports vertical or subvertical life orientation in both described species.